Gene profile of fibroblasts identify relation of CCL8 with idiopathic pulmonary fibrosis. Issue 1 (December 2017) - Lee, Jong-Uk; Cheong, Hyun; Shim, Eun-Young; Bae, Da-Jeong; Chang, Hun; Uh, Soo-Taek; Kim, Young; Park, Jong-Sook; Lee, Bora; Shin, Hyoung; Park, Choon-Sik
Abstract Background Idiopathic pulmonary fibrosis (IPF) is characterized by the complex interaction of cells involved in chronic inflammation and fibrosis. Global gene expression of a homogenous cell population will identify novel candidate genes. Methods Gene expression of fibroblasts derived from lung tissues (8 IPF and 4 controls) was profiled, and ontology and functional pathway were analyzed in the genes exhibiting >2 absolute fold changes withp -values < 0.05.CCL8 mRNA and protein levels were quantified using real-time PCR and ELISA.CCL8 localization was evaluated by immunofluorescence staining. Results One hundred seventy eight genes differentially expressed and 15 genes exhibited >10-fold change. Among them, 13 were novel in relation with IPF.CCL8 expression was 22.8-fold higher in IPF fibroblasts. The levels ofCCL8 mRNA and protein were 3 and 9-fold higher in 14 IPF fibroblasts than those in 10 control fibroblasts by real-time PCR and ELISA (p  = 0.022 andp  = 0.026, respectively). TheCCL8 concentrations in BAL fluid was significantly higher in 86 patients with IPF than those in 41 controls, and other interstitial lung diseases including non-specific interstitial pneumonia (n  = 22), hypersensitivity pneumonitis (n  = 20) and sarcoidosis (n  = 19) (p  < 0.005, respectively). Cut-off values of 2.29 pg/mL and 0.43 pg/mL possessed 80.2 and 70.7% accuracy for the discrimination of IPF from NC and the other lung diseases, respectively. IPF subjects withCCL8 levels >28.61 pg/mL showed shorter survival compared to those with lower levels (p  = 0.012).CCL8 was expressed by α-SMA-positive cells in the interstitium of IPF. Conclusions Transcriptome analysis identified several novel IPF-related genes. Among them, CCL8 is a candidate molecule for the differential diagnosis and prediction of survival.